2009
DOI: 10.1007/s11274-009-0178-0
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and antibacterial activity of some new derivatives of pyrazole

Abstract: In this study, we report the synthesis and antibacterial activity of a new series of 5-amido-1-(2,4-dinitrophenyl)-1H-4-pyrazolecarbonitriles. Our results show that all compounds exhibit antimicrobial activities against methicillin susceptible Staphylococcus aureus and methicillin resistant S. aureus with MIC values of 25.1 and 91.0 lM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 53 publications
(32 citation statements)
references
References 16 publications
0
32
0
Order By: Relevance
“…Experimental details of the tests can be found in our earlier studies. [17][18][19][20][21] The antimicrobial tests performed on compounds 3a-e and 4a-d confirmed that they are effective against both Grampositive and Gram-negative bacteria and some showed greater inhibitory activity against a number of Gram-positive and Gram-negative bacteria than the well known antibacterial agents Ampicillin and Sulfamethoxazole.…”
Section: Resultsmentioning
confidence: 79%
See 2 more Smart Citations
“…Experimental details of the tests can be found in our earlier studies. [17][18][19][20][21] The antimicrobial tests performed on compounds 3a-e and 4a-d confirmed that they are effective against both Grampositive and Gram-negative bacteria and some showed greater inhibitory activity against a number of Gram-positive and Gram-negative bacteria than the well known antibacterial agents Ampicillin and Sulfamethoxazole.…”
Section: Resultsmentioning
confidence: 79%
“…Gratifyingly, compound 3d with a butyl group was the most potent of the tested compounds against Grampositive and Gram-negative bacteria in this work and all biological research work that we have reported previously. [16][17][18][19][20][21] We propose that the chain lengths and chlorine substituent might change the binding characteristics of ligands to their respective receptors and, thereby, improve the biological activities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental details of the tests can be found in our earlier study. 21 The antimicrobial tests performed on compounds 3 and 4 confirmed that only compound 4 was effective against both Grampositive and Gram-negative bacteria, and 3 showed inhibitory activity against Gram-negative bacteria only. Also, the results revealed that new compound 4 displayed greater antibacterial activity against the tested organisms compared to the well-known antibacterial agents ampicillin and sulfamethoxazole in most cases (Table 5).…”
Section: Antibacterial Studiesmentioning
confidence: 84%
“…Pyrazole derivatives are an interesting class of organic compounds, which are found to be associated with diverse pharmacological properties such as antimicrobial [1,2], anti-inflammatory [3], antihypertensive [4], antidepressant [5], antiviral [6] and anticancer [7] activities. The synthesis and applications of these compounds have received considerable attention in recent years [8][9][10].…”
Section: Introductionmentioning
confidence: 99%